Analytical Study and Investigation of Bishop Iosif’s Androusis Mitre - Κουτσοδημητροπούλου, Μαρία (Πανεπιστήμιο Πελοποννήσου, 2017)
The present thesis investigates the Mitre of the Bishop Iosif Androusis (1770-1844). The Mitre is an elaborate bejewelled ceremonial head covering, worn only by bishops. The Mitre under study has a spherical shape and is composed of silk and cotton fabrics soaked in animal glue. It is decorated with metallic embroidery made of gilt silver (Ag), wound around a silk core, and three types of metallic sequins, some of which are coloured red. The metallic sequins are made of silver and silver-copper alloy. Different analytical methods were used, such as Optical Microscopy (OM), Scanning Electron Microscopy coupled with Energy Dispersive X-ray spectrometry (SEM/EDS), and Fourier transform infrared spectroscopy (FTIR), as the most suitable methods for the analysis of the materials of the Mitre. After the thorough investigation and identification of these materials and the documentation of the degradation signs the Mitre presents, a conservation plan was conducted including also suggestion about the most appropriate storage conditions for the Mitre.
Keywords: Ιωσήφ, Μητροπολίτης Ανδρούσης, 1775-1842; Ορθόδοξη Ανατολική Εκκλησία -- Ελλάδα -- Μητροπολίτες και επίσκοποι; Μήτρες -- Ανάλυση; Μήτρες -- Συντήρηση και αποκατάσταση; Ιωσήφ Ανδρούσης; Μήτρες επισκόπων; Συντήρηση αρχαιοτήτων